Exploration of PM mass, source, and component-related factors that might explain heterogeneity in daily PM2.5-mortality associations across the United States. (1st October 2021) - Rappazzo, Kristen M.; Baxter, Lisa; Sacks, Jason D.; Alman, Breanna L.; Peterson, Geoffrey Colin L.; Hubbell, Bryan; Neas, Lucas
Abstract: Multi-city epidemiologic studies examining short-term (daily) differences in fine particulate matter (PM2.5 ) provide evidence of substantial spatial heterogeneity in city-specific mortality risk estimates across the United States. Because PM2.5 is a mixture of particles, both directly emitted from sources or formed through atmospheric reactions, some of this heterogeneity may be due to regional variations in PM2.5 toxicity. Using inverse variance weighted linear regression, we examined change in percent change in mortality in association with 24 "exposure" determinants representing three basic groupings based on potential explanations for differences in PM toxicity – size, source, and composition. Percent changes in mortality for the PM2.5 -mortality association for 313 core-based statistical areas and their metropolitan divisions over 1999–2005 were used as the outcome. Several determinants were identified as potential contributors to heterogeneity: all mass fraction determinants, vehicle miles traveled (VMT) for diesel total, VMT gas per capita, PM2.5 ammonium, PM2.5 nitrate, and PM2.5 sulfate. In multivariable models, only daily correlation of PM2.5 with PM10 and long-term average PM2.5 mass concentration were retained, explaining approximately 10% of total variability. The results of this analysis contribute to the growing body of literature specifically focusing on assessing the underlying basis of the observed spatial heterogeneity in PM2.5 -mortality effect estimates, continuing to demonstrate that this heterogeneity is multifactorial and not attributable to a single aspect of PM. Highlights: There is spatial heterogeneity in daily PM2.5 mortality associations in the U.S. Factors related to PM mass, sources, and components are potential contributors Long-term average PM2.5, and daily PM10 correlation explained some heterogeneity